Joint Inversion of Body Wave Arrival Times, Surface Wave Dispersion Data and Receiver Functions: Method and Application to South China. Issue 9 (22nd September 2022) - Han, Shoucheng; Zhang, Haijiang; Gao, Lei; Liu, Ying; Chai, Chengping; Maceira, Monica
Abstract: We have developed a new joint inversion method that incorporates body wave arrival times, surface wave dispersion and receiver functions to simultaneously update earthquake locations and constrain three‐dimensional P ‐wave (Vp) and S ‐wave velocity (Vs) models. Due to complementary sensitivities of the three types of data, the proposed joint inversion algorithm can reduce the intrinsic non‐uniqueness of inversions using fewer types of data and better determine smooth velocity variations and velocity discontinuities. Synthetic tests demonstrate the advantages of this new joint inversion algorithm in resolving velocity structures, especially in constraining velocity gradients across the Moho interface. We have applied the proposed joint inversion algorithm to image the lithosphere velocity structure of south China. The inverted Vp and Vs models fit body wave arrival times, surface wave dispersion and receiver functions well. We further analyzed the distribution of Vs gradients across the Moho interface in detail, which helps us better understand tectonics in south China. Plain Language Summary: Seismic tomography is routinely used for imaging the heterogeneous structure of the Earth at different scales. There are different seismic tomography methods which use different types of seismic data. Typically, three types of seismic tomography methods are widely used including seismic travel‐time tomography using body wave arrival times, surface wave tomography using surface wave dispersion data, and receiver function imaging. However, different seismic tomography methods usually lead to different seismic models due to the inherent limitation of different types of seismic data and seismic tomography methods. This study has developed a new joint inversion method which is able to utilize three different types of seismic data to better constrain seismic models. Synthetic test is used to show its superiority over existing inversion methods. Then this newly developed seismic tomography method is also applied to south China to better determine its lithospheric structure, which sheds light on the geodynamics of south China block. Key Points: A new joint inversion algorithm that uses body wave arrival times, surface wave dispersion curves and receiver functions is developed The proposed joint inversion algorithm can better resolve sharp shear wave velocity variations across the Moho The distribution of shear wave velocity gradients across the Moho in south China indicates various tectonic activities around the Moho